RETRATOS CARICATOS: “Assim Os Vejo... Homens do Meu Tempo” (Palíndromo, 2013)
The following text isa short essaythataims to reportthe influenceofthe Estados de [In]certeza event tothe reflectionand reformulationof the research objectin this master’s degree program.
Keywords: estados de [in]certeza; research; caricature; montage; portrait